White blood cell count profiles in multiple sclerosis during attacks before the initiation of acute and chronic treatments - Tetsuya Akaishi (Nature Portfolio, 2021)
Abstract Multiple sclerosis (MS) is a major demyelinating disease of the central nervous system; however, its exact mechanism is unknown. This study aimed to elucidate the profile of white blood cells (WBCs) in the acute phase of an MS attack. Sixty-four patients with MS at the time of diagnosis and 2492 age- and sex-adjusted healthy controls (HCs) were enrolled. Data regarding the blood cell counts were compared between the groups. The total WBC (p < 0.0001), monocyte (p < 0.0001), basophil (p = 0.0027), and neutrophil (p < 0.0001) counts were higher in the MS group than in the HC group, whereas the lymphocyte and eosinophil counts did not differ. Adjustments for the smoking status and body mass index yielded the same results. The total and differential WBC counts of the patients with MS did not correlate with the counts of T2 hyperintense brain lesions or the levels of neurological disturbance. In summary, patients with MS showed elevated counts of total WBCs, monocytes, basophils, and neutrophils at the time of diagnosis. However, the clinical relevance of these biomarkers in the context of the development and progression of MS remains unclear.